Circ_0098181 binds PKM2 to attenuate liver fibrosis - Luo, Yuan-Yuan; Guan, Ya-Ping; Zhan, Hong-Fei; Sun, Chun-Yan; Cai, Ling-Yan; Tao, Ke-Gong; Lin, Yong; Zeng, Xin (Frontiers in Pharmacology, 2025)
BackgroundLiver cirrhosis seriously harms human health and fibrosis is the essential pathological process of cirrhosis. Recently, circular RNAs (circRNAs) were found to play critical roles in liver fibrosis, but the key circRNAs and precise mechanisms remained unclear. This study aimed to investigate the effect of circ_0098181 in fibrogenesis and explore its mechanism.MethodsRNA sequencing was conducted to identify circRNA signatures in human liver cirrhotic tissues. Hepatic stellate cells (HSCs) (including primary rat HSCs, LX2, HSC-T6) and carbon tetrachloride (CCl4) induced liver cirrhosis model were used to explore the role of circ_0098181 on HSC activation and liver fibrogenesis in vitro and in vivo. RNA sequencing, RNA pull-down, mass spectrometry, and RNA immunoprecipitation (RIP) experiments were performed to elucidate the mechanism.ResultsCirc_0098181 was obviously reduced in human fibrotic liver tissues and activated HSCs. Exogenous administration of circ_0098181 blocked the activation, proliferation, and migration of HSCs in vitro and mitigated the progression of CCl4-induced liver fibrosis in vivo. Mechanistically, adenosine deaminase acting on RNA1 (ADAR1) combined with the intronic complementary sequences (ICSs) in the flanking regions, thereby regulating the biogenesis of circ_0098181. RNA sequencing and qRT-PCR revealed the suppression of circ_0098181 on pro-inflammation cytokines expression (TNFα, Fas, Cxcl11, etc.). RNA pull-down, mass spectrometry, and RIP experiments indicated that pyruvate kinase M2 (PKM2) was the direct target of circ_0098181. Circ_0098181 bound to PKM2, restrained its nuclear translocation and phosphorylation.ConclusionIn conclusion, circ_0098181 exerts a significant anti-fibrotic effect by binding PKM2 to repress its nuclear translocation and inhibiting hepatic inflammation, suggesting the promising therapeutic merit in liver cirrhosis.